Results report: Towards a theory of media consumption value - Nina Erdmann; Lisa-Charlotte Wolter; Peter Kenning; Sylvia Chan-Olmsted; Tino Georg Konrad Meitz (IU Internationale Hochschule, 2025)
This hypothesis paper advances the conceptual groundwork for exploring the consumer perspective on media use and the perceived value of media. It addresses three central questions: (1) which theoretical foundations are available to build upon, (2) what relevant literature exists in this field, and (3) which conceptual adaptations are required to capture the specificities of media consumption. The findings provide the framework for developing the discussion guide for the first stage of empirical research, consisting of group discussions with consumers. They serve as the conceptual foundation for structuring the inquiry into how individuals evaluate media and their own media-use behaviors. The Theory of Consumption Values (TCV) (Sheth et al., 1991) forms the starting point for analyzing user motives and value perceptions across media genres. Building on this framework, the project has exploratively expanded the set of value dimensions to reflect contemporary expectations of media. These include trust (credibility, reliability, and confidence in media offerings), social gratification (belonging, connection, and community-building), resilience (stability, coping and well-being in times of uncertainty), familiarity (emotional comfort through continuity and predictability), and accessibility (the precondition of being able to access content at all). These dimensions demonstrate that media use is not only shaped by short-term aspects, but also by longterm cognitive, emotional, social, and societal values. Within the Value Media framework, this broader conceptualization allows for a more holistic assessment of media engagement and supports the development of sustainable strategies for media providers and consumers alike. Importantly, the project takes a multiplatform approach, encompassing the full spectrum of media genres. In this way, the TCV not only serves as a foundation but also demonstrates potential for theoretical advancement: by applying it to media contexts and integrating additional value dimensions, it contributes to the development of a new conceptual model - the Theory of Media Consumption Value.
Keywords: 650; Value Media; Theory of Consumption Value; Theory of Media Consumption Value; Sustainable Media; Responsible Media; Media Responsibility